IMPROVING OPERATING PERFORMANCE THROUGH MODERN TRAINING SOLUTIONS - Bartak, J.; Schwerdtfeger, M.; Pometko, S. (Science and Transport Progress, 2008)
Located in the heart of theGrenoblescientific and technological polygon, CORYS T.E.S.S. specialises in the design and production of simulators for training and studies in the energy and transport sectors. CORYS T.E.S.S. also offers training and study services and provides complementary training tools to simulators (multimedia, elearning). CORYS T.E.S.S. is a leading supplier of driving simulators for rail and urban transport with over 350 simulators operational world-wide. This article presents the different types of training simulators used in the rail and urban transport sector and the benefits they provide for improved operations and more effective training. Some recent simulator market trends and design issues that have emerged from the changing requirements of train operators and available technology are discussed.